CORRELATION BETWEEN ADHERENCE OF ANTIHYPERTENSIVE DRUGS USE AND BLOOD PRESSURE CONTROL IN PATIENTS WITH ESRD UNDERGOING HEMODIALYSIS - Tedy Kurniawan Bakri; Raihanul Akmal; Azizah Vonna; Lydia Septa Desiyana; Fitrah Sari (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2022)
Antihypertensive therapy used in patients with End-Stage Renal Disease undergoing hemodialysis is objected to decrease mortality related to ESRD complications. Nonadherence to antihypertensive therapy can lead to uncontrolled blood pressure. This study aims to determine the level of adherence to antihypertensive drugs and its correlation to blood pressure control in ESRD patients undergoing hemodialysis. It was an observational analytic study based on the cross-sectional method. Sixty Â person subjects were involved using the quota sampling technique. The level of adherence was examined using the Modified Morisky Scale questionnaire. Blood pressure data were obtained from mean values of respectively pre, during, and post-hemodialysis blood pressure within four hemodialysis visitations. The data was examined bivariately using the Chi-square test with a 95% confidence interval. The results show most patients have high level of adherence to antihypertensive treatments (55%) yet have uncontrolled levels of blood pressure (95%). The Chi-square analysis found there is no significant relationship between the level of adherence to antihypertensive therapy and the average blood pressure level of ESRD patients who undergo hemodialysis (p-value 0,301). This finding suggests a consideration in monitoring the effectivity of hypertension management that adherence is not a single significant factor affecting the successfulness of medication.